Mathematical literacy of senior high school students in Yogyakarta - Rosalia Hera Novita Sari; Ariyadi Wijaya (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2017)
The aim of this research is to describe mathematical literacy of Senior High School students in Yogyakarta. This research was a survey using quantitative design. The population was all of Senior High School students in Yogyakarta. The sampling was a combination of stratified random sampling and cluster random sampling. The sample was 813 students the 10th grade of Senior High School. These schools include high, average and low category based on the score in the national examination of mathematics subject. The data collection was by a test. The student was tested with 13 items of mathematical literacy problems. The analysis of those data used descriptive statistics including mean, standard deviation, maximum and minimum score, total score, and also test statistics z (). The research finding reveals that mathematical literacy of Senior High School students in Yogyakarta is in a very low category. Mathematical literacy of Senior High School students for understanding indicator belong to low category and for the other indicators of process belongs to very a low category.